Pengaruh Motivasi Kerja dan Kompetensi Kerja Terhadap Kinerja Pegawai Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Sidenreng Rappang - Angka, Tenri; F, Fadlina; Salam, Mifta Farid (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the Influence of Work Motivation and Work Competence on Employee Performance at the Human Resources Development and Personnel Agency (BKPSDM) of Sidenreng Rappang Regency. This type of research is associative quantitative research. The sampling technique used is saturated sampling. The sample of this study was all employees at the Human Resources Development and Personnel Agency (BKPSDM) of Sidenreng Rappang Regency totaling 45 people. Data were obtained from primary data and secondary data. Data collection techniques used were observation, questionnaires and documentation. Hypothesis testing was carried out using multiple linear regression tests. Data processing used SPSS version 26 software. Based on the results of the tests carried out, it showed that the work motivation variable did not have a positive and insignificant effect on employee performance because the significant value of the t-test results (0.414) was greater than 0.05. The work competence variable had a positive and significant effect on employee performance because the significant value of the t-test results (0.000) was less than 0.05. Meanwhile, the variables of work motivation and work competence have a positive and significant effect on employee performance because the significant value of the f-test results (0.000) is smaller than 0.05. It is recommended for further researchers who want to study the same problem or phenomenon to be able to add other variables and indicators, use other methods, and add social theories to strengthen the arguments presented.